2022
DOI: 10.3390/ani12212953
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Optimal In-Feed Amino Acid Ratio for Japanese Quail Breeders Based on Utilization Efficiency

Abstract: The description of the genetic potential is the first step to estimating amino acid requirements and the ideal amino acid relation (IAAR). The aim of this study was to estimate the parameters that describe the daily maximum theoretical nitrogen retention (NRmaxT, mg/BWkg0.67), daily nitrogen maintenance requirement (NMR, mg/BWkg0.67), protein quality (b), dietary efficiency of the limiting amino acid (bc−1) and determine the lysine requirement and the IAAR for Japanese quail breeders. Two nitrogen balance assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…The dietary threonine concentration reported for laying quails are estimated higher than those determined in this study for Japanese quail breeders. In agreement with our result in the current study, dThr requirement for Japanese quail breeders was estimated at 0.59% (Carvalho et al, 2022, 2023), which was 14% and 5% lower than reported by Ramalho de Lima et al (2013) and Sarcinelli et al (2020), respectively. Carvalho et al (2022) concluded that Japanese quail breeders have lower dietary efficiency than commercial birds.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The dietary threonine concentration reported for laying quails are estimated higher than those determined in this study for Japanese quail breeders. In agreement with our result in the current study, dThr requirement for Japanese quail breeders was estimated at 0.59% (Carvalho et al, 2022, 2023), which was 14% and 5% lower than reported by Ramalho de Lima et al (2013) and Sarcinelli et al (2020), respectively. Carvalho et al (2022) concluded that Japanese quail breeders have lower dietary efficiency than commercial birds.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our result in the current study, dThr requirement for Japanese quail breeders was estimated at 0.59% (Carvalho et al, 2022, 2023), which was 14% and 5% lower than reported by Ramalho de Lima et al (2013) and Sarcinelli et al (2020), respectively. Carvalho et al (2022) concluded that Japanese quail breeders have lower dietary efficiency than commercial birds. This difference maybe elucidated by the different between present commercial quails.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations